O romântico contemporâneo - Ariel Ferreira Costa (2015)
The Romantic Contemporary is a survey of some aspects of romanticism who crossed modernity and still prevalent in contemporary art, especially the similarities between art and life, the Landscape, reflections on the creative subjectivity, art criticism and the notion of Sacred. Developed artwork and exposed by the author between 2005 and 2014 will be used as an opportunity for thinking critically. For both are called theorists such as Walter Benjamin, Giorgio Agamben, Georges Bataille and Boris Groys. The reflections are addressed to an art form which dispenses with art objects, such as performances, actions and artistic interventions in public space, which are known through photographic records and textual narratives. The spaces of the city of BeloHorizonte in the early twenty-first century as the Praça 7, downtown streets, the paved streams and the crowd are the political sociological and historical ground where are the majority of works narrated.